Supplemental Material for Zuccolo et al., 2022 - Andrea Zuccolo (14293642); Sara Mfarrej (10304834); Mirko Celii (13798065); Saule Mussurova (5190311); Luis F. Rivera (14293645); Victor Llaca (25464); Nahed Mohammed (8295957); Arnab Pain (37809); Abdulmajeed Fahad Alrefaei (8968607); Abdulwahed Fahad Alrefaei (9579672); Rod A. Wing (118040) (2023)
Falcon2_CDS_omicsbox_gene.gff: description of the locations and structures of the predicted genes FALCON_TE_LIBRARY_V3_no_repbase.fa: multifasta file containing the TE library used in this work (excluding entries from Repbase)